Poly I:C-induced maternal immune activation causes schizophrenia-like behaviors in the offspring of both sexes by regulating gut microbiota and tryptophan metabolism pathway - Xu, Zhilong; Hu, Canrun; Luo, Yayan (Frontiers in Microbiology, 2025)
Prenatal polyinosinic-polycytidylic acid (Poly I:C) exposure-induced maternal immune activation (MIA) causes schizophrenia-like abnormal behaviors in offspring. Extensive evidence suggests that patients with schizophrenia exhibit gut microbiota dysbiosis and tryptophan (TRP) metabolism dysregulation, which is correlated with psychotic and cognitive symptoms. However, the role of gut microbiota and TRP metabolism in Poly I:C MIA-induced schizophrenia-like behaviors is unclear. In this study, pregnant C57/BL6 mice were injected with Poly I:C (20 mg/kg) or vehicle at gestational day (GD) 9. We found that prenatal Poly I:C exposure at GD 9 led to gut microbiota dysbiosis, thereby activating the TRP-kynurenine (KYN)-quinolinic acid (QA) pathway in the hippocampus, serum, and feces, inhibiting the hippocampal and serum TRP-KYN-kynurenic acid (KYNA) pathway and the hippocampal, serum, and fecal TRP-5-hydroxytryptamine (5-HT) pathway, thus leading to anxiety- and depression-like behaviors and impairments in prepulse inhibition (PPI) and recognition memory in female and/or male offspring during adolescence and/or adulthood. In addition, prenatal Poly I:C exposure caused sex-dependent changes in QA levels and gut microbiota composition in offspring. These results suggest that gut dysbiosis may contribute to prenatal Poly I:C exposure-induced schizophrenia-like behaviors by disturbing the TRP metabolism pathway in adolescent and adult offspring of both sexes. Our study indicates possible strategies for ameliorating prenatal Poly I:C exposure-induced schizophrenia-like behaviors. Our findings provide additional evidence that gut microbiota dysbiosis is an underlying mechanism for Poly I:C MIA-induced schizophrenia-like behaviors and behavioral impairments in schizophrenia. Given the sex-related differences in gut microbiota and QA levels, both sexes should be included in studies that explore the mechanisms of Poly I:C MIA-induced schizophrenia-like behaviors.